Intentional Replantation of a Mandibular Premolar as Treatment for Lower Lip Paresthesia: A Case Report - Hamedi, Ali; Jafarzadeh, Hamid; Bonyadimanesh, Fateme (Iranian Endodontic Journal, 2022)
Paresthesia can result from some post-endodontic problems, including bacterial infections or mishaps which occur during the cleaning, shaping, and filling of the root canal. There are pharmacological and instrumental methods for the treatment of paresthesia; however, if presenting symptoms are suggestive of nerve injury, surgical approaches, such as intentional replantation, could be considered. In this case report study, we treated paresthesia that had occurred after endodontic treatment using intentional replantation. This case report describes the use of intentional replantation of a mandibular premolar as a successful technique to treat paresthesia involving the lower lip.